Request and Politeness Strategies in the Javanese-Speaking Generation Z Community: A Pragmatic Study - Yeasy Agustina Sari; Suhono, Suhono (Bulletin of Science Education, 2024)
The aim of this research is to analyze the use of Request and Politeness Strategy used by the Generation Z Community of Javanese Language Speakers and to analyze the choice of Request and Politeness Strategy used by the Generation Z Community of Javanese Language Speakers. This research uses qualitative research by using descriptive methods. This research uses a pragmatic approach with an analytical method using Trosborg and Blum Kulka's theory. The sample for this research is 50 people in the Javanese-speaking Gen Z community. The data for this research are the results of the Discourse Completion Test (DCT) in the written form. The result shows that the use of Request Strategy and Politeness Strategy is used by the Generation Z Community of Javanese Language Speakers, in the Request Strategy in the Lower to Higher Category including Ability/Willingness, Statements of Speaker's Wishes and Desires, Statements of Speaker's Needs and Demands, Hint. Then in the Request Strategy Category, the Higher to Lower Category includes Ability/Wilingness, Statements of Speaker's Needs and Demands, Imperative, Obligation and Necessity, Be Pessimistic, Apologize. This research has an impact on efforts to ensure that the Javanese language does not only act as a means of communication, but is also a very important part of self-identity in the context of national and global interactions. Likewise, the perception that the use of regional languages ​​can hinder progress can be overcome by spreading awareness that the individuals who are developing today are those who remain true to their cultural and social character